1988
DOI: 10.1063/1.341044
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of the ZnSe/GaAs system grown by molecular-beam epitaxy

Abstract: We report the results of an investigation of the structural properties and relaxation of misfit stress with transmission electron microscopy and x-ray diffraction techniques. Epitaxial films of ZnSe were grown on GaAs by molecular-beam epitaxy of thicknesses ranging from 0.05 to 4.9 μm. The films contain stacking fault defects up to thicknesses of about 150 nm. Above 150 nm perfect misfit dislocations are generated from surface sources and the stacking fault defects to accommodate the lattice mismatch. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(44 citation statements)
references
References 15 publications
3
40
1
Order By: Relevance
“…and the critical thickness (hc ) for other arrangements of dislocations, including that for complete relaxation of misfit by an array of misfit dislocations [5]. In observations of dislocations in {001} later structures, the equilibrium Lomer array is found only for very large misfits or for h » h c [5,9,10]. Instead, 1/2(110) dislocations form on inclined {111} planes and glide to deposit on interface.…”
Section: Resultsmentioning
confidence: 99%
“…and the critical thickness (hc ) for other arrangements of dislocations, including that for complete relaxation of misfit by an array of misfit dislocations [5]. In observations of dislocations in {001} later structures, the equilibrium Lomer array is found only for very large misfits or for h » h c [5,9,10]. Instead, 1/2(110) dislocations form on inclined {111} planes and glide to deposit on interface.…”
Section: Resultsmentioning
confidence: 99%
“…25,36,37 For example, Petruzello et al 25 found by high-resolution transmission microscopy that most MDs in ZnSe/GaAs (001) were 60°dislocations lying in the interface parallel to h110i directions, but one sample also exhibited kinks at which MDs changed line direction from 110 ½ and 110 Â Ã : Chen et al 36 studied ZnSe/GaAs (001) by transmission electron microscopy and also found that most MDs were parallel to h110i directions in the interface, but they also observed some irregular dislocations tending along [100] and [010] directions. An important underlying assumption here is that dislocations are predominantly of 60°t ype on {111} glide planes, and that dislocations with other geometries have a negligible effect on the observed x-ray diffraction profiles.…”
Section: Methodsmentioning
confidence: 97%
“…24 However, the total thickness of the ZnSe buffer was chosen so that it would be less than the experimentally determined critical layer thickness. 25,26 The graded ZnS y Se 1Ày was grown at 360°C with 39 mW/cm 2 photoirradiation. (A neutral density filter with 63% transmission was used.)…”
Section: Methodsmentioning
confidence: 99%
“…The total thickness of the two ZnSe buffer layers was varied from 135 to 270 nm, in order to span the pseudomorphic/ nonpseudomorphic transition. 22 ZnSySe1_y was grown on top of the ZnSe buffer layers at a temperature of 360 or 400~ and with the incident irradiation intensity adjusted to 36 mW/cm 2 or 12 mW/cm 2, for a growth time of 45 min. The reactant mole fractions were 10 4 (DMZn), 2 to 4 • 10 -~ (DMSe) and 0 to 6 • 10 4 (DES).…”
Section: Methodsmentioning
confidence: 99%